The Psychological Aspects in Countee Cullen’s Selected Poems - Yousif , Shaymaa (Al-Adab Journal, 2025)
Poetry serves as a transparent medium that reflects the realities of individuals or society. Throughout his poetic career, Countee Cullen (1903-1946) addresses subjects such as political violence, sexual desire, religion, childhood, and memories. To explore these themes, this research delves into the psychological interpretation of three of Cullen’s selected poems: "Heritage" (1925), "Incident" (1925) and "From the Dark Tower" (1927), By applying a psychological analytical approach, the study discloses the hidden reasons, desires, and motives behind these works in relevant lines from the above selected poems. The research concludes that poetry can act as a window that shows the inner feelings, thoughts, and motives, both conscious and unconscious. In Cullen’s case, his poems reveal a deeply personal response against the extremes of discrimination and racism he experienced.